Neurotransmitter system gene variants as biomarkers for the therapeutic efficacy of rTMS and SSRIs in obsessive-compulsive disorder - Chu, Lingjun; Wu, Yidan; Yin, Jiajun; Zhang, Kai; Zhong, Yiwen; Fan, Xiwang; Wang, Guoqiang (Frontiers in Psychiatry, 2024)
Purpose: This study aims to examine the potential influence of RS4680 (COMT), RS16965628 (SLC6A4), and RS1019385 (GRIN2B) polymorphisms on the therapeutic response to repetitive transcranial magnetic stimulation (rTMS) and selective serotonin reuptake inhibitors (SSRIs) in individuals with obsessive-compulsive disorder (OCD).Patients and methods: Thirty-six untreated outpatients diagnosed with OCD were recruited and allocated to active or sham rTMS groups for two weeks. The mean age of the participants was 31.61, with 17 males (47.22%) and 19 females (52.78%). Peripheral blood samples (5 mL) were collected from each participant using ethylenediaminetetraacetic acid (EDTA) vacuum tubes for genotyping purposes, clinical evaluation was taken place at baseline and second week.The A allele of RS4680, C allele of RS16965628, and GG allele of RS1019385 were identified as potential bio-markers for predicting treatment response to OCD treatments (rTMS & SSRIs).Those genes may serve as bio-markers for the combined treatment of rTMS and SSRIs in OCD. The finding hold promise for further research and the potential implementation of precision treatment of OCD.